2022
DOI: 10.1155/2022/9436186
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of Water Intake, Hydration Status, and Related Hydration Biomarkers among Physically Active Male Young Adults in Beijing, China: A Cross-Sectional Study

Abstract: Studies on the water intake of athletes in daily life are insufficient. The objective was to determine the water intake and hydration status among physically active male young adults. In this cross-sectional studies study, 111 physically active male young adults were recruited. The amount of daily total drinking fluid intake (TDF) among participants was recorded and evaluated in real time over 7 days using the “7-day 24-hour fluid intake questionnaire” (liq. In 7). The daily water intake from food (WFF) was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…The main result was that plain water was the main source of TFIs in all four groups, accounting for 78.8~100.00%. This was consistent with the results obtained for adults and children living in China [ 38 , 44 , 48 , 61 , 62 , 63 , 64 ]. Dairy products were the second-highest contributors among participants in all four groups, although the amount of milk (median: 64 mL) was considerably lower than the amount recommended by the Chinese Nutrition Society (300 mL).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The main result was that plain water was the main source of TFIs in all four groups, accounting for 78.8~100.00%. This was consistent with the results obtained for adults and children living in China [ 38 , 44 , 48 , 61 , 62 , 63 , 64 ]. Dairy products were the second-highest contributors among participants in all four groups, although the amount of milk (median: 64 mL) was considerably lower than the amount recommended by the Chinese Nutrition Society (300 mL).…”
Section: Discussionsupporting
confidence: 93%
“…The blood biomarkers did not change significantly with different TFIs in each group, since only the width of the platelet volume distribution and percentage of monocytes differed. This was in agreement with the results obtained by a study conducted in Beijing that determined that the urine and blood biomarkers of young men differed in groups with different fluid intake levels [ 61 ]. Several studies have also shown that blood indicators are good markers for assessing dehydration status in individuals; however, these were not sensitive to a mild hydration status [ 69 ].…”
Section: Discussionsupporting
confidence: 92%
“…Urine osmolality, urine speci c gravity (USG), pH, urea, and creatinine, urine electrolyte concentrations (including sodium, potassium, chloride, calcium, magnesium, and phosphate) were tested with standard procedure, which was described in our previous study [35]. Fasting venous blood samples were collected with standard procedure by trained investigators to measure the concentrations of Na, K, and Cl, and testosterone, cortisol, creatinine, and copeptin, which had been described in our previous study.…”
Section: Urine and Plasma Biomarkersmentioning
confidence: 99%
“…While, in China, few studies evaluating the body composition among young adults were conducted [23,[31][32][33], but not among the athletes, and the associations between water intake and body composition were not explored yet, which needed more attention. Besides, large proportions of athletes were not in euhydration status in China [34,35], which may cause deleterious effects on performances, especially in the hot weather. To date, the differences of body compositions of athletes with different hydration statuses were not investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…The primary methodological concern is that total water intake is not necessarily indicative of hydration status. In healthy young men with initial total water intake below 2 L/day, the required time to reach sufficient hydration status is over 4 weeks accompanied by an increase in total water intake of more than 0.5 L/day . This finding is pertinent because, based on the European Food Safety Authority’s reference values for total water intake for adolescents older than 14 years, about 64.4% of girls and 69.4% of boys in the “Healthy Lifestyle in Europe by Nutrition in Adolescents” cross sectional study have a total water intake below the recommended amount of 2.5 and 2.0 L/d, respectively .…”
mentioning
confidence: 99%